Implementasi Strategi Diskusi Kelompok Berbasis Active Learning Terhadap Hasil Belajar Siswa pada Materi Fikih - Muhamad Hisyam Iskandar; Masripah; Nenden Munawaroh (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the application of active learning-based group discussion strategies in improving student learning outcomes in the subject of Fiqh in grade XI of SMA Darussalam Wanaraja. The study used a qualitative descriptive approach with Islamic Religious Education teachers and grade XI students selected through purposive sampling. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. Data validity was tested through triangulation of sources and techniques. The results showed that heterogeneously designed group discussion strategies were able to increase student active participation, courage to express opinions, group cooperation, and understanding of Fiqh material. Increased student involvement resulted in better learning outcomes, where most students achieved scores above the Minimum Completion Criteria (KKM). Obstacles that emerged were differences in student academic abilities and limited learning time, but these could be overcome through structured classroom management, group mentoring, and continuous motivation. Thus, active learning-based group discussion strategies can be an effective learning alternative to improve student learning outcomes in the subject of Fiqh.